2016
DOI: 10.1016/j.jtcme.2014.11.038
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the anti-inflammatory activity of the aqueous and ethanolic extracts of the leaves of Albizzia lebbeck in rats

Abstract: Albizzia lebbeck Benth. (Mimosaceae) is a medicinal tree used to treat several inflammatory ailments in the Indian traditional Ayurvedic system of medicine. The aim of the present study was to evaluate the possible anti-inflammatory activity of the aqueous (AE) and ethanolic (EE) extracts of the leaves of A. lebbeck to support the ethnopharmacological claims. The study was carried out using Wistar rats (100–150 g). The AE and EE were prepared using the Soxhlet extraction process. The anti-inflammatory activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 23 publications
2
38
0
Order By: Relevance
“…In the final or cellular phase, leukocytes migrate to the inflamed area [14]. Prostaglandins play a crucial role in the cellular phase, which takes place after about four hours following the intra-plantar administration of carrageenan [15]. The present study showed that the rats injected with carrageenan (0.1 mL, 1% in 0.9%, sub-planter) exhibited increased paw thickness, an indication of paw inflammation, when measured at hourly intervals for 5 h and at 24 h after injection.…”
Section: Effects Of T Algeriensis and T Fontanesii Extracts On Carrmentioning
confidence: 99%
“…In the final or cellular phase, leukocytes migrate to the inflamed area [14]. Prostaglandins play a crucial role in the cellular phase, which takes place after about four hours following the intra-plantar administration of carrageenan [15]. The present study showed that the rats injected with carrageenan (0.1 mL, 1% in 0.9%, sub-planter) exhibited increased paw thickness, an indication of paw inflammation, when measured at hourly intervals for 5 h and at 24 h after injection.…”
Section: Effects Of T Algeriensis and T Fontanesii Extracts On Carrmentioning
confidence: 99%
“…The results in our study show that in experi- This effect is registered after both single and multiple For selective COX-2 inhibitors, however, pro-thrombotic state is typical because they block the production of prostacyclin (PGI2) but not that of thromboxane A2 (since TXA2 synthesis depends on preserved COX-1 activity). 9,32 Compound 3d does not affect red blood cell and platelet levels. It suppresses white blood cells after 14-…”
Section: Discussionmentioning
confidence: 93%
“…Prostaglandins play a major role in the cellular phase, which occurs approx. 4hours after intraplantar administration of carrageenan 32.…”
mentioning
confidence: 99%
“…and several other plants [118][119][120][121]. Beta-sitosterol D-glucoside has many pharmacological activities [118][119][120][121][122][123][124] such as androgenic, antiadenomic, anticancer [129][130][131][132][133][134], antiedemic [135], and antiinflammatory [136][137][138][139][140][141][142]. Sitosterol has a structure such as cholesterol that later in the body can become the precursor of testosterone and The maximum score of the addition is eight [40,94] has been supposed to have an antifertility, and sex steroids have been implicated in the development and maintenance of Benign prostatic hyperplasia (BPH) and use of androgen reducing compounds, such as 5α-reductase inhibitors which block the conversion of testosterone into dihydrotestosterone [14,32,52].…”
Section: Discussionmentioning
confidence: 99%